Human herpesviruses in the cornea. Issue 6 (1st June 2000) - Kaye, Stephen B; Baker, Kevin; Bonshek, Richard; Maseruka, Henry; Grinfeld, Esther; Tullo, Andrew; Easty, David L; Hart, Colin A
Abstract : AIMS: To determine the sensitivity and specificity of culture, immunohistochemistry (IHC), the polymerase chain reaction (PCR), and in situ hybridisation (ISH) for detecting herpes simplex virus (HSV-1) in the cornea of patients undergoing penetrating keratoplasty. To compare the incidence of HSV-1 in the cornea with that of varicella zoster virus (VZV), cytomegalovirus (CMV), and Epstein-Barr virus (EBV). METHODS: The corneas of 110 patients, 52 with a documented history of herpes keratitis (HSK) and 58 with non-herpetic corneal disease, were investigated using IHC, PCR, ISH, and culture. RESULTS: HSV-1 DNA and antigen were detected in 82% and 74% respectively, of corneas of patients with HSK and in 22% and 15% of corneas of patients with no history of HSK. The sensitivity of PCR and IHC was 82% and 74% with a specificity of 78% and 85%, respectively. HSV-1 DNA and antigen were found more frequently and in increased amounts in corneas of patients with a short interval between their last attack of HSK and surgery. There was a good correlation between PCR and IHC in 71%. HSV-1 was isolated by culture in 2%. Latency associated transcripts were not detected using ISH. Evidence of VZV DNA or antigen was found significantly more frequently in the corneas of patients with a history of HSK (p<0.001). No evidence of EBV or CMV was found in any cornea. CONCLUSIONS: PCR and IHC are both sensitive for the detection of HSV-1 in the cornea. A combination of PCR and IHC increases the specificity for the diagnosis of HSK to 97%. HSV-1 appears to be slowly removed from the cornea. VZV and HSV-1 may co-infect the cornea.